Sponsors’ motivation to consistently crowdfund projects - P.K, Vivek; Gupta, Deepak (International Journal of Engineering and Technology, 2018)
Crowdfunding is fast emerging as a viable financing method in this digital age as a solution that allow businesses, individuals or organiza-tions to raise capital in the form of either investments or donations from a number of individuals.Â As of now, two models have been applied by platforms for reward based crowdfunding projects - the subscription based model and the project based model. Project based model follows the traditional method of a sponsor supporting a project one time during the crowdfunding period. Subscription based model on the other hand is a new model followed by crowdfunding platforms like Drip and Patreon where they ask sponsors to repeatedly fund projects on a monthly basis. In this study a comparison was done between the two models to understand motivational factors that would attract sponsors to fund an idea in each of these models. For this a conceptual model was developed after an extensive literature review. The moti-vation drivers include interest, reward, relationship, recognition, playfulness and philanthropy. The model was tested using primary data collected through a pan-India survey involving 178 respondents. The data was analyzed using the ordered logistic regression model. Our analysis shows that relationship and playfulness have a positive impact on a sponsorâ€™s intention to fund projects in a subscription based model. This signifies a need for integrated communication channel between sponsors and creators. The comparison of the two models also showed relationships, rewards, interest and philanthropy motivations differentially impacting the project based model as compared to the subscription based model.Â Â Â